High-performance silver nano conductive particle and preparation method and photovoltaic application thereof
By using the aromatic aroma of silver perchlorate and phenolic hydroxyl groups in the reaction system to replace monocarboxylic acid and amine, and the low-temperature sintering method, the problems of self-polymerization and dispersion in the preparation of traditional silver nanoparticles are solved, and the preparation of high-performance silver nanoconductive particles and photovoltaic applications are realized.
Patent Information
- Application Number
- CN202510010860.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The silver nanoparticles prepared by the traditional liquid phase reduction method have self-polymerization, large resistance and uneven dispersion. The silver nanoparticles prepared by the gas phase method have high cost and complex particle size control.
Silver perchlorate is used as the silver source, and the reduction and coordination effect of monocarboxylic acids replaced by aromatic aromatic containing phenolic hydroxyl groups, and under the catalytic action of amine, the reaction system is sintered at low temperature to prepare high-performance silver nanoconductive particles.
The uniform particle size distribution, good dispersion and high conductivity of silver nanomaterials are achieved, and the problems of self-polymerization and dispersion in traditional methods are overcome, and the preparation cost is reduced.
Smart Images

Figure CN119811743A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and specifically relates to high-performance silver nano-conductive particles, a preparation method thereof, and photovoltaic applications. Background Art
[0002] Silver nanomaterials, with their unique physical and chemical properties such as excellent high conductivity, significantly high specific surface area, abundant active sites and stable current density, are important electrode materials for silicon-based solar cells, integrated circuits, etc., and have wide application potential in new generation optoelectronic devices such as organic and perovskite. With the rapid development of high-efficiency and low-cost solar cell technology and high-performance electronic device technology, the requirements for the fineness, dispersion and conductivity of silver nanoparticles are increasing day by day.
[0003] In the current preparation process of conductive silver paste, the silver powder particles required are large and uneven, and the silver paste contains solvents and additives that require high-temperature annealing. This feature is different from the modern processing technology of electronic devices, which not only restricts the overall performance of the device, but also the performance of the device is closely related to the quality of the film formed by the silver particles, increasing the amount of silver used. Therefore, by selecting a silver source with a special counter anion and introducing a specific ligand, the morphology and self-assembly behavior of silver nanoparticles can be cleverly adjusted, thereby significantly improving the quality of the film. In the synthesis and preparation process of silver nanoparticles, in addition to the silver source and ligand, the selection of reducing agent is also crucial. A variety of reducing agents such as citrate, ascorbic acid, polyphenolic acid, sodium borohydride and polyols provide rich possibilities for the synthesis of silver nanoparticles of different morphologies and sizes. However, the silver nanoparticles prepared by the traditional liquid phase reduction method often have strong self-aggregation, large resistance, and are difficult to achieve uniform dispersion. In contrast, although the silver nanoparticles prepared by the gas phase method have excellent dispersibility, their high cost and complexity of particle size control limit their wide application.
[0004] In view of this, the present invention proposes a new liquid phase reduction preparation scheme. Summary of the invention
[0005] To solve the problems raised in the above background, the present invention aims to solve the key problems of increased resistance and uneven particle dispersion caused by self-aggregation of silver nanomaterials during the preparation process, and to provide high-performance silver nano-conductive particles, a preparation method thereof, and photovoltaic applications.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing high-performance silver nano-conductive particles, using silver perchlorate as a silver source, reducing and coordinating an aromatic substituted monocarboxylic acid containing a phenolic hydroxyl group, and sintering the reaction system at low temperature under the catalysis of an amine to obtain high-performance silver nano-conductive particles.
[0008] The concentration of silver perchlorate in the reaction system is 0.01-1 g / mL (preferably 0.01-0.05 g / mL). Silver perchlorate is selected because, on the one hand, it has a large solubility in water and common organic polar solvents, a high yield and is easier to generate nanoparticles with uniform particle size; on the other hand, the mutual solubility of perchlorate and organic compounds improves the activity of the reduction reaction.
[0009] The concentration of the aromatic substituted monocarboxylic acid containing phenolic hydroxyl group is 0.001-0.1 g / mL (preferably 0.001-0.005 g / mL), and the molar ratio of amine to silver perchlorate is between 0.01-100 (preferably 1-50).
[0010] The aromatic substituted monocarboxylic acid containing a phenolic hydroxyl group is a compound represented by formula (I),
[0011]
[0012] In the formula, m is 0 or 1, n is 1, 2 or 3, and R is selected from C1-C 20 Alkyl chain, C1-C 20 Alkoxy chain, C1-C 20 Silane chain, C1-C 20 Alkylsulfide chain, C1-C 20 The amino chain, C2-C 20 Alkenyl chain, C2-C 20 The alkynyl chain of
[0013] Ar is selected from any one of the following structures:
[0014]
[0015] The amine used is one or more of primary amine, secondary amine, tertiary amine, quaternary ammonium salt, quaternary ammonium base. Preferably, one or more of ethylamine, ethanolamine, diethylamine, triethylamine, dimethylethanolamine, methylbenzenedimethylammonium chloride, trimethylammonium bromide, dodecyltrimethylammonium hydroxide and didecyldimethylammonium hydroxide.
[0016] Specifically, silver perchlorate (a) is fully dissolved in a solvent, and then an aromatic substituted monocarboxylic acid (b) containing a phenolic hydroxyl group is added under stirring to form a mixed solution, which is then fully stirred, and then an amine (c) is added thereto. After the addition, the obtained reaction solution is centrifuged, the supernatant is removed, and a precipitate is left to obtain high-performance silver nano-conductive particles. Then, a solvent is added to the precipitate to wash it repeatedly, and the above steps are repeated to disperse the final product in deionized water to obtain an aqueous dispersion containing high-performance silver nano-conductive particles.
[0017] The stirring speed after adding the silver perchlorate solution to the aromatic substituted monocarboxylic acid containing phenolic hydroxyl group needs to be controlled at 50-1000 rpm, and the stirring time is strictly controlled at 5-20 min; the stirring speed after adding the amine is controlled at 50-1000 rpm, and the stirring time is strictly controlled at 30-60 min.
[0018] After the amine is added, the pH value during the reaction is controlled to be 4-11, and the reaction is carried out at room temperature for 1-10 hours.
[0019] The reaction solution after adding the amine is centrifuged at a speed of 3000-8000 rpm, preferably 5000 rpm, and the precipitate is collected. The precipitate is washed with one or more of deionized water, methanol or ethanol, and the washing is repeated several times.
[0020] The solvent for dissolving silver perchlorate is one of methanol, ethanol, deionized water, chloroform, chlorobenzene, toluene, ethyl acetate and acetone, among which deionized water is preferably used.
[0021] The solvent for dissolving the aromatic substituted monocarboxylic acid containing phenolic hydroxyl group is one of methanol, ethanol, deionized water, chloroform, chlorobenzene, toluene, ethyl acetate and acetone, among which deionized water is preferred. The aromatic substituted monocarboxylic acid containing phenolic hydroxyl group is used as a dispersant and a reducing agent in the reaction process.
[0022] Selection of amine compounds: If deionized water is selected as the solvent, the amine compounds need to be soluble in water. Amine compounds are used as alkaline catalysts in the reaction process. For the amine solvent, it is more appropriate to use a solvent that can dissolve carboxylic acid and add it dropwise to the amine solvent. The two solvents can be the same or different, such as methanol and deionized water, or methanol and ethanol.
[0023] A high-performance silver nano-conductive particles prepared by the method are spherical high-performance silver nano-conductive particles prepared by the method.
[0024] A high-performance silver nano-conductive material is prepared by directly spraying a dispersion containing the high-performance silver nano-conductive particles onto a substrate surface by a spray coating method, and then sintering at a low temperature to obtain a film of the high-performance silver nano-conductive material with complete morphology.
[0025] The low temperature sintering is performed at an annealing temperature ranging from 100 to 150° C. and an annealing time ranging from 5 to 30 minutes.
[0026] An application of the above-mentioned is the application of the above-mentioned high-performance silver nano-conductive particles or the above-mentioned conductive material in optoelectronic devices.
[0027] The high-performance silver nano-conductive particle dispersion is sprayed and sintered at low temperature to prepare a high-performance conductive film, which can be used as an electrode in optoelectronic devices, and the application scenarios include but are not limited to solar cells, electroluminescent devices, field effect transistors, and detectors.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The invention provides a class of high-performance silver nano conductive materials. The nano materials have good dispersibility and electrical properties and are a class of excellent conductive materials.
[0030] (1) The preparation method provided by the present invention reduces silver perchlorate, an aromatic substituted monocarboxylic acid containing a phenolic hydroxyl group, and a complex amine compound under strict process conditions to obtain a silver nanoconductive material. Characterization confirms that the silver nanomaterial prepared by the method has a uniform particle size distribution and good dispersibility, which effectively overcomes the self-aggregation problem of silver nanomaterials in traditional preparation methods.
[0031] (2) The high-performance silver nano-conductive material prepared by the present invention has excellent processing performance, and can be conveniently prepared into an electrode material with excellent conductive performance by spraying, scraping, screen printing and other technologies combined with a low-temperature sintering process. This invention broadens the application scope of silver nano-materials in the field of conductive electrode preparation, and provides strong support for the conservation of battery electrodes and the miniaturization of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The technical solution of the present invention is further described below with reference to the attached drawings and tables and through specific implementation methods.
[0033] Figure 1 This is an image of the particle size distribution of the silver nanomaterial synthesized in Example 1 of the present invention.
[0034] Figure 2 This is a SEM image of the silver nanomaterial synthesized in Example 1 of the present invention.
[0035] Figure 3This is the Zeta potential image of the silver nanomaterial synthesized in Example 1 of the present invention.
[0036] Figure 4 This is the XRD image of the silver nanomaterial synthesized in Example 1 of the present invention.
[0037] Figure 5 FTIR images of the silver nanomaterial synthesized in Example 1 of the present invention before and after annealing. DETAILED DESCRIPTION
[0038] In order to better illustrate the present invention, the technical solution of the present invention is further illustrated by specific embodiments below, and the examples given do not limit the protection scope of the present invention:
[0039] The high-performance silver nano-conductive material obtained by the present invention is silver nano-particles with good dispersibility, and is further uniformly coated on a substrate by spray coating technology to form a high-conductivity film, and is successfully applied to electronic devices. The preparation method of the present invention retains the low-cost advantage of the liquid phase reduction method, and effectively solves the coagulation and dispersion problems of silver nano-particles, thereby significantly improving the performance of electronic devices.
[0040] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0041] The experimental materials, reagents, etc. used in the following experimental examples can be obtained through commercial channels or known experimental methods.
[0042] Example 1: Preparation of Gallic Acid-Based Silver Nanoparticle Slurry
[0043] Add 0.3g of gallic acid to 100mL of deionized water, stir at 750rpm for 10 minutes. Add 0.3g of silver perchlorate to 20mL of deionized water, stir at 750rpm for 10 minutes. Add the silver perchlorate aqueous solution drop by drop into the stirring gallic acid aqueous solution, stir at 750rpm for 10 minutes. Add 20μL of dimethylethanolamine solution (the molar ratio of acid to amine is 20:1) and continue stirring for 1 hour. Centrifuge three times with deionized water, and add 1mL of deionized water to the prepared product for dispersion and storage.
[0044] The invention characterizes the prepared silver nanomaterial. The particle sizes of 100 silver nanomaterials are measured by a nano laser particle size analyzer, wherein the average value of the particle size distribution of the sample is called the average particle size. The average particle size of the prepared silver nanomaterial is 47nm, which is approximately uniform particle size distribution. Figure 1 The particle size distribution diagram of the silver nanomaterial is shown in FIG. 1 . A peak value is observed in the range of 35-65 nm, which has a narrow distribution. For the aqueous dispersion of the silver nanomaterial, the silver nanomaterial has no flocculation phenomenon and has good dispersibility. Figure 2 This is an image observed by Gemini SEM360 scanning electron microscope (SEM). The prepared nanomaterial has a spherical morphology. The gallic acid anions around the synthesized silver nanomaterial have a negative Zeta potential of -46.23mV ( Figure 3 ), with strong aggregation resistance. X-ray diffraction (XRD) measurements were performed using a Bruker D8Advance instrument ( Figure 4 ), the crystal diffraction peaks indicate that the crystal phase purity of the synthesized silver nanomaterials is high. There are no diffraction peaks of silver oxide or other impurities in the spectrum, indicating that no silver-containing byproducts are produced during the annealing process. The annealing process improves the crystallinity of the silver nanoparticles, which helps to improve their stability and conductivity. The sintering process was characterized by Fourier transform infrared (FTIR) spectroscopy using TM4000 Plus ( Figure 5 ). The hydroxyl group in gallic acid can form a coordination bond with silver, and the negatively charged carboxyl group can form an ionic bond with silver through electrostatic interaction. -1 and 777cm -1 The peaks on the left and right also disappeared, indicating that decarboxylation occurred during the annealing process. During this process, gallic acid and its oxidation products were almost removed from the surface of silver nanoparticles. High-temperature heating is conducive to the carbonization of organic matter, which is consistent with the rapid increase in conductivity with increasing temperature.
[0045] Comparative Example 1: Preparation of Gallic Acid-Based Silver Nanoparticles by Adjusting the Dropping Speed and Stirring Speed
[0046] Add 0.3g of gallic acid to 100mL of deionized water, stir at 750rpm for 10 minutes. Add 0.3g of silver perchlorate to 20mL of deionized water, stir at 750rpm for 10 minutes. Quickly drop the silver perchlorate aqueous solution into the stirring gallic acid aqueous solution, stir at 2000rpm for 10 minutes. Add 20μL of dimethylethanolamine solution (the molar ratio of acid to amine is 20:1) and continue stirring for 1 hour. Centrifuge three times with deionized water, and add 1mL of deionized water to the prepared product for dispersion and storage.
[0047] Comparative Example 2: Preparation of Gallic Acid-Based Silver Nanoparticles with Adjusted Reaction Time
[0048] Add 0.3g of gallic acid to 100mL of deionized water, stir at 750rpm for 10 minutes. Add 0.3g of silver perchlorate to 20mL of deionized water, stir at 750rpm for 10 minutes. Quickly drop the silver perchlorate aqueous solution into the stirring gallic acid aqueous solution, stir at 1500rpm for 10 minutes. Add 20μL of dimethylethanolamine solution (the molar ratio of acid to amine is 20:1) and continue stirring for 8 hours. Centrifuge three times with deionized water, add 1mL of deionized water to the prepared product for dispersion and storage.
[0049] Example 2: Preparation of Caffeic Acid-Based Silver Nanoparticle Slurry
[0050] Add 0.44g of caffeic acid to 100mL of deionized water, stir at 800rpm for 10 minutes. Add 0.3g of silver perchlorate to 20mL of deionized water, stir at 800rpm for 10 minutes. Add the silver perchlorate aqueous solution drop by drop into the stirring caffeic acid aqueous solution, stir at 800rpm for 5 minutes. Add 10μL of dimethylethanolamine solution (the molar ratio of acid to amine is 10:1) and continue stirring for 0.5 hours. Centrifuge three times with deionized water, add 1mL of deionized water to the prepared product and disperse and store it.
[0051] Example 3: Preparation of silver nanoparticle conductive electrode
[0052] The silver nanoparticle aqueous dispersion prepared in the above-mentioned embodiments and comparative examples was coated on a film, annealed at different temperatures under a standard atmospheric pressure, and dried. The conductivity was then measured. The results are shown in the following table.
[0053]
[0054] It can be clearly seen from the above table data that by using aromatic substituted monocarboxylic acids containing phenolic hydroxyl groups (taking gallic acid and caffeic acid as examples) as ligands and reducing agents and following the experimental process of the present invention, a high 6S / m conductivity, this performance ranks among the best in the current low-temperature sintered silver nanoparticle conductive materials. Compared with the comparative example, when the drip stirring conditions and reaction time are adjusted, the conductivity decreases significantly. This result shows that in the synthesis process, the control of the drip stirring conditions and reaction time is crucial, which will have a significant impact on the dispersion, uniformity and self-aggregation characteristics of the material. Further, through a detailed analysis of the conductivity at different sintering temperatures, the silver nanoparticles prepared by the present invention show an obvious inflection point in conductivity at 130°C, verifying that the ligand undergoes a decarboxylation reaction at the sintering temperature and is effectively removed, which is consistent with the characterization analysis results in Example 1. It is particularly worth mentioning that the sintering temperature of 130°C belongs to the category of low-temperature sintering in the field of optoelectronic devices. Therefore, the silver nanoparticles of the present invention are more suitable for electrode treatment of optoelectronic devices, showing its broad application prospects in this field.
[0055] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing high-performance silver nano-conductive particles, characterized in that: Silver perchlorate is used as the silver source, and high-performance silver nano-conductive particles are obtained by low-temperature sintering of the reaction system under the catalysis of amines through the reduction and coordination of aromatic substituted monocarboxylic acids containing phenolic hydroxyl groups.
2. The method for preparing high-performance silver nano-conductive particles according to claim 1, characterized in that: The concentration of silver perchlorate in the reaction system is 0.01-1 g / mL, the concentration of the aromatic substituted monocarboxylic acid containing phenolic hydroxyl groups is 0.001-0.1 g / mL, and the molar ratio of amine to silver perchlorate is between 0.01-100.
3. The method for preparing high-performance silver nano-conductive particles according to claim 1, characterized in that: The aromatic substituted monocarboxylic acid containing a phenolic hydroxyl group is a compound represented by formula (I), In the formula, m is 0 or 1, n is 1, 2 or 3, and R is selected from C1-C 20 Alkyl chain, C1-C 20 Alkoxy chain, C1-C 20 Silane chain, C1-C 20 Alkylsulfide chain, C1-C 20 The amino chain, C2-C 20 Alkenyl chain, C2-C 20 The alkynyl chain of Ar is selected from any one of the following structures:
4. The method for preparing high-performance silver nano-conductive particles according to claim 1, characterized in that: The amine is one or more of a primary amine, a secondary amine, a tertiary amine, a quaternary ammonium salt, and a quaternary ammonium base.
5. The method for preparing high-performance silver nano-conductive particles according to any one of claims 1 to 4, characterized in that: Silver perchlorate (a) is fully dissolved in a solvent, and then added to an aromatic substituted monocarboxylic acid (b) containing a phenolic hydroxyl group under stirring conditions to form a mixed solution, which is fully stirred after mixing, and then an amine (c) is added thereto. After the reaction, the reaction solution is centrifuged, the supernatant is removed, and a precipitate is left to obtain high-performance spherical silver nano-conductive particles, and then a solvent is added to the precipitate for repeated washing, and the above steps are repeated to disperse the final product in deionized water to obtain an aqueous dispersion containing high-performance silver nano-conductive particles.
6. The method for preparing high-performance silver nano-conductive particles according to claim 5, characterized in that: The stirring speed after adding the silver perchlorate solution to the aromatic substituted monocarboxylic acid containing phenolic hydroxyl group needs to be controlled at 50-1000 rpm, and the stirring time is strictly controlled at 5-20 min; the stirring speed after adding the amine is controlled at 50-1000 rpm, and the stirring time is strictly controlled at 30-60 min.
7. The method for preparing high-performance silver nano-conductive particles according to claim 5, characterized in that: The reaction solution after adding the amine is centrifuged at a speed of 3000-8000 rpm, and the precipitate is collected and washed with one or more of deionized water, methanol or ethanol, and the washing is repeated several times.
8. A high-performance silver nano-conductive particle prepared by the method of claim 1, characterized in that: Spherical high-performance silver nano-conductive particles are prepared according to the method of claim 1.
9. A high-performance silver nano-conductive material, characterized in that: The dispersion containing the high-performance silver nano-conductive particles according to claim 1 or the dispersion containing the high-performance silver nano-conductive particles according to claim 1 is directly sprayed onto the surface of the substrate by a spray coating method, and a film of high-performance silver nano-conductive material with complete morphology can be obtained by low-temperature sintering.
10. A use according to claim 8 or 9, characterized in that: The use of the high-performance silver nano-conductive particles described in claim 8 or the conductive material described in claim 9 in optoelectronic devices.